1998
DOI: 10.1021/la980845c
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Effects on Properties of Cationic Vesicles

Abstract: The effect of counterion nature and concentration on phase transition, bilayer structure, vesicle size, vesicle internal volume per mole of amphiphile, and surface potential is evaluated for cationic vesicles composed of dioctadecyldimethylammonium (DODA) acetate, chloride, or bromide. Over a range of ionic strengths (0−5 mM monovalent salt), no interdigitation was detected in the bilayer structure for the three DODA counterions. The preferential type of aggregate formed from self-assembly of DODA salts is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
64
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 34 publications
14
64
1
5
Order By: Relevance
“…When the PMAO concentration is further increased the ζ-potential weakly decreases. This fact agrees very well with results obtained by other authors [49,50]. In these works, the combination of light scattering and ζ-potential measurements indicated that the zeta-potential often decreases with increasing the vesicle radius.…”
Section: Electrophoretic Mobility Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…When the PMAO concentration is further increased the ζ-potential weakly decreases. This fact agrees very well with results obtained by other authors [49,50]. In these works, the combination of light scattering and ζ-potential measurements indicated that the zeta-potential often decreases with increasing the vesicle radius.…”
Section: Electrophoretic Mobility Resultssupporting
confidence: 93%
“…One of the most interesting results found was that mixed vesicles of Aerosol OT and poly(allylamine) become unstable when the electric charge of vesicles is not completely neutralized. This behavior was interpreted using the Volegol's [50,51] model. This model considers that the non-uniform distribution on the surface electric charge due to the highly correlated adsorption of the polyelectrolyte on the vesicle surfaces induces attractive interactions between vesicles that finally flocculate even though the surface charge of vesicles is not completely neutralized.…”
Section: Discussionmentioning
confidence: 99%
“…DODAB is a bilayer-forming cationic lipid that tends to form large unilamellar vesicles (LUV's) in excess water [47,48]. It features a hydrophobic moiety consisting of a double acyl chain (C18:0) attached to a quaternary ammonium headgroup (one single positive charge per molecule) [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Small DODAB BF, (73 AE 1) nm mean diameter and (45 AE 3) mV mean zeta-potential were prepared above the mean phase transition temperature of the DODAB bilayer (45 C) 25 by probe sonication (80-90 mW, 10 min, above 70 C) in 1 mM NaCl Milli-Q water solution at ca., 2.0 mM DODAB as previously described. 18 The sonicated dispersion was centrifuged at 10,000 g/15 C /40 min, to eliminate titanium residues ejected from the tip.…”
Section: Preparation Of Dodab Dispersions and Determination Of Dodab mentioning
confidence: 99%